Comparison of urine Gram stain and urine culture to diagnose urinary tract infection in children - Amalia Utami Putri; Oke Rina; Rosmayanti Rosmayanti; Rafita Ramayati; Rusdidjas Rusdidjas (Paediatrica Indonesiana, 2013)
Background Urinary tract infection (UTI) are due to pathogeninvasion of the urinary tract. The upper or lower tract may beaffected, depending on the presence of infection in the kidney,or bladder and urethra. Infection of urinary tract affect up to10% of children and are the most common bacterial infection ininfants and young children worldwide. The prevalence of UTI is3-5% in girls and 1 % in boys. Urine culture is considered to bethe gold standard diagnostic test for UTI. However, Gram stainsof uncentrifuged urine have been done in rural health centers andlaboratories in peripheral areas that lack facilities to evaluate urinespecimens. Gram stains of urine may be an effective method forruling out UTI in rural health center patients, thus saving timeand money in impoverished settings.Objective To compare urine Gram stain and urine culture asdiagnostic tests for UTI in children.Methods This cross-sectional study was held in H. Adam MalikHospital from May to June 2010. The 54 participants were aged0 - 14 years, suspected to have UTI and recruited by consecutivesampling. Urine was collected after the external urethral orificewas cleaned. A drop of the urine specimen was Gram stainedand examined by a light microscope, while the remainder of thespecimen was used for laboratory urine cultures. If Gram negativebacteria were observed by Gram stain, we considered the subjectto have UTI.Results The sensitivity and specificity of urine Gram staincompared to urine culture were 88% and 100%, respectively. Thepositive predictive value (PPV) and negative predictive value(NPV) were 100% and 90%, respectively.Conclusion Urine Gram stain may be a good alternative to urineculture for diagnosing UTI in children living in areas with limitedhealth care facilities.